Studi Empiris Aplikasi Sistem Informasi Akuntansi (SIA), Literasi Keuangan dan Praktek Akuntansi Manajemen terhadap Kinerja Bisnis UMKM Kota Semarang - Kiki Yulianti; Jaluanto Sunu Punjul Tyoso (Jurnal Ekonomi Manajemen Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an essential component of Indonesia's economic framework. MSMEs need to improve their business performance stability to maintain economic stability. This research aims to determine the influence of accounting information systems, financial literacy, and management accounting practices on MSME business performance in the city of Semarang. The population of this research is 187 MSMEs, with a sample of 100 MSMEs that have more than 5 employees (purposive sampling method). The findings show that the variables SIA (Accounting Information System) and PAM (Management Accounting Practices) have a significant positive impact on KB (Business Performance), indicating that any increase in these variables will enhance MSME business performance. Conversely, the LK (Financial Literacy) variable has a negative and insignificant impact on KB, indicating that many MSMEs do not fully understand financial literacy in terms of knowledge and benefits. However, LK and SIA have a significant positive impact on PAM, demonstrating that optimal PAM implementation supports MSME business performance. There is a significant positive indirect effect of LK and SIA on PAM and KB, highlighting the importance of financial literacy and accounting information systems in improving MSME business performance.